Dielectric, Polarization and Strain Response of Enhanced Complex Ceramics: The Study through Pb(Zr0.52Ti0.48)O3-SrBi2Ta2O9 - Orapim Namsar (2018)
Copyright © 2015 Taylor and Francis Group, LLC. Electrical properties of the (1-x)PZT-xSBT ceramics (0.1≤x≤0.3) were investigated in comparison with pure PZT and SBT ceramics. It was found that the dielectric constant increased with small addition of SBT (x = 0.1) into PZT. The hysteresis loop measurement demonstrated that the PZT-SBT ceramics showed larger remanent polarization than pure PZT and less coercive filed than pure SBT ceramic. Strain behavior showed a symmetric butterfly curve in the compositions with 0≤x≤0.3 but the low strain obtained was found in pure SBT. This research suggested that 0.9PZT-0.1SBT ceramic is a promising material to be further utilized in ferroelectric memory devices.